Prevalence and Factors Associated With Compliance With COVID-19 Presidential Lockdown Measures: A Cross-Sectional Study - Emmanuel Olal MPH; David Mukunya PhD; Johnson Nyeko Oloya MD; Steven Baguma MD; Christopher Okot MMED; Nelson Onira Alema MMED; Denis Acullu MMED; Denish Omoya Ochula MPH; Pamela Okot Atim MMED; Patrick Olwedo Odong MPH; Godfrey Smart Okot MMED; Francis Pebalo Pebolo MMED; et al. (SAGE Publishing, 2023)
The coronavirus disease 2019 (COVID-19) is one of the most severe global health uncertainties to date. Although significant global effort has been put into implementing COVID-19 pandemic control measures such as lockdowns, travel restrictions, and hygiene precautions, the transmission is expected to resurface once these efforts are discontinued. We aimed to determine the prevalence and factors associated with compliance with presidential 53-day lockdown measures in June-July 2021 in northern Uganda. In this cross-sectional study, 587 adult participants (≥18 years old) from northern Uganda were selected using a systematic sampling method. Data collection involved interviewer-administered questionnaires with an internal validity of Cronbach's α = .72. Socio-demographic characteristics of participants were described, and multivariable modified Poisson regressions were performed to assess prevalence ratios between dependent and selected independent variables, with respective P values at 95% confidence intervals. All analyses were conducted using Stata 17.0. Participants' compliance with the presidential lockdown directives was high at 88%(95% CI: 85%-90%). Compliance with the presidential directives was more likely among participants who agreed to the lockdown measures [adjusted Prevalence Ratio, aPR = 1.28 (95% CI: 1.10-1.49; P  = .001)] compared to those who did not, and more likely among those who were afraid of death from COVID-19 [aPR = 1.08 (95% CI: 1.01-1.15; P  = .023)] than those who did not. However, compliance was less likely among males [aPR = 0.91 (95% CI: 0.86-0.97; P  = .002)] compared to females, those aged 35 to 44 years [aPR = 0.87 (95% CI: 0.79-0.97; P  = .013)] compared to those less 25 years; and unmarried [aPR = 0.89 (95% CI: 0.82-0.97; P  = .011)] compared to the married. Compliance with the COVID-19 presidential lockdown measures in northern Uganda was high. The factors associated with compliance were the fear of death and agreement with presidential lockdown measures. However, compliance was less likely among males, unmarried persons, and persons aged 35 to 44. The authors recommend more community engagements, participation, sensitization, mobilization, and simultaneous application of multiple public health approaches to improve compliance and control of COVID-19.